Preparing controlled low strength materials with cement-treated construction waste clay improved by sodium hexametaphosphate - Chenhao Li; Tinglong Xie; Jianwen Ding; Jian Tang; Mengying Gao (PLoS ONE, 2025)
To solve the disposal of large quantities of construction waste clay, this study proposes a new method for preparing controlled low strength materials (CLSM). Flow tests, unconfined compressive strength (UCS) tests, hydraulic conductivity tests and scanning electron microscope (SEM) analyses were performed on cement-treated construction waste clay with different additive content (e.g. sodium hexametaphosphate (SHMP), water glass, and phosphogypsum (PG)). The influence of additive content on the mechanical and microstructural properties of cement-treated clay-based CLSM was analyzed. The results indicated that the SHMP greatly enhanced the flowability of samples, adding 1%SHMP increased the fluidity of the sample by more than 80%, whereas 5% water glass had negligible effect. Additionally, the 10% PG improved the flowability retention, making it have higher flowability after 30 mins (more than 200 mm). SHMP interacted with Ca2+, significantly influencing the cement hydration; notably, 1% content resulted a notable reduction of samples from 167.5 kPa to 21.5 kPa at 1 day. Although increasing SHMP content improved the early strength, it led to a decrease in later strength, with the maximum late strength observed at 2% SHMP. Both PG and water glass also contributed to late strength enhancement, though higher SHMP levels diminished their effects. While SHMP markedly improved permeability resistance (less than 8 × 10−8 cm/s after 28d), hydraulic conductivity showed minimal variation with increased dosage. The combination of SHMP, PG and water glass effectively enhances the flowability and strength of clay-based CLSM at low water content, solving the contradiction between fluidity and strength. This promotes the sustainable development of green building materials.